Guideline for multiple sclerosis treatment in Brazil: Consensus from the Neuroimmunology Scientific Department of the Brazilian Academy of Neurology - Comini-Frota, Elizabeth Regina; Vasconcelos, Cláudia C. F.; Mendes, Maria Fernanda (Arquivos de Neuro-Psiquiatria, 2017)
Multiple sclerosis has become an ever-increasing challenge to neurologists. With the release of the latest medications on the market, Brazilian neurologists feel divided between following their patients’ evolution in accordance with the strict rules established by the Brazilian Ministry of Health regarding drug distribution, or following disease progression and worsening in accordance with the evidence in the literature. Therefore, a systematic review of the main published treatment guidelines was conducted and an escalating therapy proposed for guiding multiple sclerosis patient treatment in Brazil.
Keywords: multiple sclerosis; Consensus; treatment